Investigation of Dormancy Breaking and Water Uptake Mechanisms in Majidea zangueberica Kirk ex Oliv., Markhamia lutea (Benth.) K. Schum., Tabebuia aurea (Silva Manso) Benth. and Hook. f. ex S. Moore, Santalum album L., and Morinda citrifolia L. seeds. - S, Preethi Jenifer Praticia.; M, Kanchana. (Asian Journal of Biological and Life Sciences)
Aim: The primary aim of this research is to analyze the conditions that prompt dormancy release and identify the primary water gap location during the dormancy-breaking process. By subjecting the seeds to various dormancy-breaking techniques, we observed that water ingress occurred exclusively through the lens due to the dislodgement of two sclereid layers. Background: Water uptake is a vital process for seed germination. However, in these seeds, a water-impermeable seed coat, while beneficial for adapting to the environment, hinders germination without appropriate treatment. Nevertheless, the factors triggering dormancy release, along with varying interpretations of the specialized seed coat structure known as the “water gap”, remain unresolved for seeds such as Maijidea zangueberica Kirk ex Oliv., Markhamia lutea (Benth) K. Schum., Tabebuia aurea (Silva Manso) Benth. and Hook.f.ex S. Moore, Santalum album L., and Morinda citrifolia L. Materials and Methods: Seed moisture content was measured using a high constant temperature oven dry method followed by dormancy assessment and identification of water gap by SEM analysis. Results: The storage life of Tabebuia aurea seeds was extended, substantiated by a notably low moisture content of 4.22%, here by SEM analysis the lens regions adopted circular or lid-like shapes, maintaining structural integrity in the hilum and micropyle regions whereas in Majidea zangueberica, where a blister-like aspect resembling. Conclusion: This research has provided details on the period in which seeds with impermeable seed coverings and low moisture content can be stored. These can be seen to time their germination to best coincide with the growing season.
Keywords: Moisture content; Physical dormancy; Storage life; Water gap